Impact of Green Transformation Leadership on Environmental Knowledge Learning and Work Pro-environmental Behaviors: The Mediating Role of Green Self-efficacy and Green Creativity - Qasim , Awais; Pandi , Oyyapan Durai; Saleem , Farida; Danila, Nevi (Journal of Ecohumanism, 2024)
The purpose of this study is to investigate the Impact of GTL (Green Transformation Leadership) on Environmental Knowledge Learning and WPB (Work pro-environmental Behaviors) through the mediating role of green self-efficacy and green creativity. The study has adopted a survey-based approach where data were collected from 279 employees working in hotel industry of Saudi Arabia using structured questionnaires and validated scales. Results show that GTL directly impacts EKL and WPB, suggesting it promotes the acquisition of environmental knowledge and skills, and GTL encourages employees to participate in friendly environmental behaviors in the workplace. This result also found, GSE and GC mediate the relationship between GTL and both EKL and WPB. This suggests that GTL not only directly influences EKL and WPB but also indirectly through its impact on GSE and GC. Future studies could discover the long-term effects of leadership on environmental sustainability, examine the role of leadership in fostering innovation and adaptation to environmental challenges, and examine the influence of different leadership styles on specific environmental behavior.